2017
DOI: 10.15632/jtam-pl.55.1.343
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to thermal and mechanical stresses in a FGM cylinder with exponentially-varying properties

Abstract: A novel approach is employed to a general solution for one-dimensional steady-state thermal and mechanical stresses in a hollow thick cylinder made of a functionally graded material (FGM). The temperature distribution is assumed to be a function of radius, with general thermal and mechanical boundary conditions on the inside and outside surfaces of the cylinder. The material properties, except Poisson's ratio, are assumed to be exponentially-varying through the thickness. Forcing functions applied to the inner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…As it causes lower variation between the inner and outer walls, it can be concluded that MC 2 is more suitable because of keeping circumferential stress stable along the wall thickness. These results also agree with the findings of Celebi et al (2017) and Eslami et al (2005). Because of the geometric difference, the results obtained for the spherical body are lower compared with the cylindrical body.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…As it causes lower variation between the inner and outer walls, it can be concluded that MC 2 is more suitable because of keeping circumferential stress stable along the wall thickness. These results also agree with the findings of Celebi et al (2017) and Eslami et al (2005). Because of the geometric difference, the results obtained for the spherical body are lower compared with the cylindrical body.…”
Section: Resultssupporting
confidence: 90%
“…They have mainly examined the effects of the elastic moduli, Poisson ratio and the thermal expansion coefficient of two constituents on the results. Celebi et al (2016Celebi et al ( , 2017) carried out the one-dimensional steady-state thermal and mechanical stresses analysis for a thick cylinder/sphere made of exponentially graded materials by complementary functions method. An analytical solution of clamped-clamped thick-walled FG cylinder with power-law varying material properties in radial directions is discussed in Gharooni et al (2016)'s study for deformations and stresses under internal pressure and thermal loading.…”
Section: Introductionmentioning
confidence: 99%
“…The production of such materials requires the use of advanced technologies during their production [1]. Due to the high costs of obtaining the coatings and the functionality that should be met by such materials, they require the development of some accurate modeling methods, both numerical and analytical, allowing forecasting of temperature, heat flux, displacement and stress distribution with the expected accuracy of calculations [2].…”
Section: Introductionmentioning
confidence: 99%
“…The major aim of this research is to show an effective and correct resolution technique. CFM is an effective and basic resolution procedure with a theoretic background in the written works [28,29] The technique is effectively employed to structures such as curved rods [30], composite beams [31], cylinders [32,33], spheres [34] and annular fin [35,36] with different structural mechanical problems.…”
Section: Introductionmentioning
confidence: 99%